The Milan school of foraminiferal micropalaeontology - M.R. Petrizzo; I. Premoli Silva; M. B. Cita (Geological society for the micropalaeontological society, 2013)
Studies of foraminifera in Milan are dated back to the 1940s and have been carried out since the 1950s, when a formal course in micropaleontology was introduced within the Masters degree in geology. Since the early days, the school of Milan has conducted landmark research projects from the Mesozoic to the Quaternary with a multidisciplinary approach, contributing to the development of modern biostratigraphy, chronostratigraphy, biochronology and to the definition of the stratotypes, and playing a fundamental role in deep ocean explorations. Over the years, foraminifera, and especially planktonic foraminifera, have been extensively investigated in terms of species diversification and evolution, enhancing their validity for dating and correlating rocks, and their links to palaeoceanographic changes. An overview of the main achievements of the Milan school of micropalaeontology is presented in this paper. Among them are the delineation of the geological evolution of the Mediterranean Sea in the Neogene, including the studies that proved the Late Miocene deep-sea desiccation, the development of an integrated bio-, magneto-, chemo- and cyclostratigraphy that has provided the main basis for the geological timescale used today, and the insights into the evolution of planktonic foraminifera and into the linkages between biotic and chemostratigraphic changes that occurred during times of oceanic dysoxia and extreme climates in the Mesozoic and Palaeogene.